2012
DOI: 10.1007/s00267-012-9812-y
|View full text |Cite
|
Sign up to set email alerts
|

Land Degradation at the Stara Planina Ski Resort

Abstract: The environmental impacts of ski resorts in the Balkan region are great and can lead to landscape degradation and loss of land functionality. In this study, we present an example of the negative effects of human activities at the Stara Planina ski resort in southeastern Serbia. The objective of this study is detailed analysis of the characteristics of environmental impacts at the Stara Planina. The management of the ski area and ski slope development caused severe degradation of topsoil and native vegetation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 33 publications
1
28
0
1
Order By: Relevance
“…Scott et al (2003) noted that ski areas should be closed if the maximum temperature is greater than 10 • for 2 consecutive days accompanied by liquid precipitation. Additionally, skiers may also choose not to ski at extremely low temperatures (below ∼ −25 • ) (Tervo, 2008;Rutty and Andrey, 2014). Because snowmaking has been used as an adaptive strategy to compensate for the decrease in snow reliability worldwide, temperatures between −2 and −5 • were taken as optimal conditions in regard to efficient snowmaking (Tervo, 2008).…”
Section: Air Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Scott et al (2003) noted that ski areas should be closed if the maximum temperature is greater than 10 • for 2 consecutive days accompanied by liquid precipitation. Additionally, skiers may also choose not to ski at extremely low temperatures (below ∼ −25 • ) (Tervo, 2008;Rutty and Andrey, 2014). Because snowmaking has been used as an adaptive strategy to compensate for the decrease in snow reliability worldwide, temperatures between −2 and −5 • were taken as optimal conditions in regard to efficient snowmaking (Tervo, 2008).…”
Section: Air Temperaturementioning
confidence: 99%
“…Following previous studies (Scott et al, 2003;Tervo, 2008;Rutty and Andrey, 2014), the daily mean air temperature was reclassified into 11 regimes with corresponding scores (Table 2), and the air temperature index was the mean score for the 2010-2014 ski seasons (Fig. 1c).…”
Section: Air Temperaturementioning
confidence: 99%
“…In addition, snowmaking facilities have been used to improve the capability of ski resorts to cope with climate change (Han and Han, 2001;Daniel et al, 2008;Steiger and Mayer, 2008;Rixen et al, 2011;Pons-Pons, 2012;Berghammer et al, 2014). The water quality in artificial snow, the air quality, and soil and vegetation conditions are also important factors affecting the development of ski resorts (Catherine et al, 2003;Kubota and Shimano, 2010;Caskey, 2011;Ratko et al, 2012). With increasing demands for comfort from skiers, scholars have begun to emphasize human factors affecting the development of ski resorts, including ski resort operation (Andrew, 1998;David and Alphonse, 1998;Pintar et al, 2009), local cultures (Landauer et al, 2014), traffic and the environment (Sanjay, 2002;Du, 2012;Li, 2015) and event tourism (Getz, 2008;Zhang and Yang, 2014;Li, 2015).…”
Section: Development Of An Evaluation Index Systemmentioning
confidence: 99%
“…However, one study reported high plant species diversity and occurrence of uncommon, tall herb species in areas where the canopy closure was low, such as under gondola lifts, at the edge of ski-slopes and on ski slopes, as opposed to nearby undisturbed forest (Kubota and Shimano 2010). Ski slopes can still have some ecological similarity, in terms of species and functional diversity, to nearby forest (Burt and Rice 2009), but landscape fragmentation can be substantial (Ristic et al 2012).…”
Section: Creation and Machine-grading Of Ski Slopesmentioning
confidence: 99%
“…The creation and machine grading of ski slopes impact the vegetation and soil through the higher susceptibility to erosion (arrow 5; Delgado et al 2007;Kangas et al 2012;Ristic et al 2012), because the removal of vegetation and rocks or removal of the top soil layer removes physical barriers to runoff and damages the soil physical structure (Burt and Rice 2009). Due to the sparser vegetation cover and increased soil density through compaction, especially graded ski slopes are more sensitive to soil erosion and surface runoff.…”
Section: Erosion Riskmentioning
confidence: 99%